Glycation: a new hope in targeting hepatocellular carcinoma? - Leung, Christopher; Angus, Peter W.; Forbes, Josephine M. (Translational Cancer Research, 2017)
Hepatocellular carcinoma (HCC) is the second most common cause of cancer mortality worldwide and is the most rapidly growing indication for liver transplantation globally. There is, therefore, an urgent need to explore novel areas which may be contributing to pathogenesis such as advanced glycation pathways, to better understand HCC progression. Advanced glycation end-products (AGEs) are a group of biologically active compounds that are formed when sugar moieties react non-enzymatically with amino groups. They are abundant in Western diets and found endogenously at an increased rate in diabetes. This article will summarise the association between AGEs in liver disease and HCC progression. In elucidating mechanisms in HCC pathogenesis, the underlying aetiologies are important with viral hepatitis, alcoholic and non-alcoholic liver disease being the most common causes. Future directions lie in elucidating mechanism with disease specific in vivo animal models and complementary in vitro studies. A consideration of multiple AGE receptors as well as AGE effects on gut microbiota inflammatory pathways is also important. Ultimately, translational research in glycation pathways involved in HCC may offer novel biomarkers to detect early HCC or monitor disease progression. It may also provide important dietary insights into prevention and generate targets for novel pharmacotherapy.